2017
DOI: 10.7717/peerj.3308
|View full text |Cite
|
Sign up to set email alerts
|

The density and biomass of mesozooplankton and ichthyoplankton in the Negro and the Amazon Rivers during the rainy season: the ecological importance of the confluence boundary

Abstract: The boundary zone between two different hydrological regimes is often a biologically enriched environment with distinct planktonic communities. In the center of the Amazon River basin, muddy white water of the Amazon River meets with black water of the Negro River, creating a conspicuous visible boundary spanning over 10 km along the Amazon River. Here, we tested the hypothesis that the confluence boundary between the white and black water rivers concentrates prey and is used as a feeding habitat for consumers… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…The CCA ordination analysis revealed that the considerable variations in different mesozooplankton groups among sampling stations were significantly correlated with the variations of temperature, conductivity, and nitrate concentrations. This confirms with the observations in other areas, where the water temperature was a keystone element in the seasonal dynamics of mesozooplankton (Jerling and Weerts, 2018;Nakajima et al, 2017), and may regulate most ecological mechanisms in temperate areas (Sellami et al, 2010). As mentioned by El-Tohamy (2018a), the study area receives relatively high anthropogenic disturbance, directly or indirectly resulting in high values of nutrients and conductivity.…”
Section: Discussionsupporting
confidence: 90%
“…The CCA ordination analysis revealed that the considerable variations in different mesozooplankton groups among sampling stations were significantly correlated with the variations of temperature, conductivity, and nitrate concentrations. This confirms with the observations in other areas, where the water temperature was a keystone element in the seasonal dynamics of mesozooplankton (Jerling and Weerts, 2018;Nakajima et al, 2017), and may regulate most ecological mechanisms in temperate areas (Sellami et al, 2010). As mentioned by El-Tohamy (2018a), the study area receives relatively high anthropogenic disturbance, directly or indirectly resulting in high values of nutrients and conductivity.…”
Section: Discussionsupporting
confidence: 90%
“…This dynamic allows the transport of organisms to flooded wetlands, with high productivity and complex habitats (e.g. aquatic macrophytes), which favors biological recruitment (Nakajima et al., 2017; Oliveira et al., 2020; Stuart & Sharpe, 2020; Zacardi et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These ecotones function as a key habitat structure and work as filters in the dispersion of fish in river systems, influencing changes in species composition at small spatial scales (Czeglédi et al., 2016; Thornbrugh & Gido, 2010). In addition, they constitute spatial elements of the organization and structuring of fish populations in the different phases of their life cycle (Kiffney et al., 2006; Nakajima et al., 2017). They also act as important feeding and spawning areas for several species of migratory fish of economic importance, widely exploited by commercial and subsistence fishing in the Amazon (Barthem et al., 2016; Zacardi, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations